Analisis Kasus Wanprestasi Dalam Transaksi Jual Beli Secara “Online” - Ramadhani, Dwi Aryanti; Dewani, Citranti Hanifah; Nurhayati, Elsa; Zaini, Noer Gita Safira; Rahmadhani, Swastika (Media Hukum Indonesia (MHI), 2024)
Agreements in e-commerce and ordinary agreements are not much different, the only difference is the form and application. Default is a term taken from the Dutch word wanprestatie which means failure to fulfill achievements or obligations in an agreement. In this study the author analyzes the court decision regarding default in online / e-commerce sales and purchase agreements, namely Decision Number 629/Pdt.G/2020/PN JKT.SEL" The results of this study show that the legal remedies taken by the Plaintiff for the breach of contract carried out after carry out an analysis regarding the elements of the default committed, evidence is needed and the application of relevant articles that will be used in the dispute resolution process. The legal remedy taken by the Plaintiff for breach of contract was that the Plaintiff gave a warning via subpoena from the Plaintiff's Attorney 2 (two) times, dated 10 and 22 July 2020, where in the first (first) subpoena the Defendant only sent 265 bags on 19 July 2020. Because the Defendant was uncommitted and inconsistent, the Plaintiff filed a lawsuit against the Panel of Judges to examine and decide on the case, punishing the Defendant to obey and submit to the decision/determination of the District Court. The Plaintiff also calculated and based on the law requested that the Defendant return the Plaintiff's money including the obligation to pay an administrative fine of 1.5% (One point five percent) of the Total Transaction.